2007
DOI: 10.1016/j.ejcts.2007.06.024
|View full text |Cite
|
Sign up to set email alerts
|

Primary lung cancer and extrapulmonary malignancy

Abstract: In cases of operability, standard resection must be the method of choice, because of its best survival rates. The results support the demand of an exact and short-term oncological care system to detect early stages of SPLC for patients operated upon for tumors at different sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 24 publications
2
12
0
Order By: Relevance
“…For example in the studies referenced above, 1 excluded patients with any history of cancer [10], 1 included patients with a history of smoking related cancers [8], 1 excluded patients with a history of cancer within 5 years, 1 excluded patients with a history of renal cancer, melanoma or breast cancer [14], while 2 excluded most cancer patients with exception of non-melanomatous skin cancer, and in-situ carcinoma of the bladder [2], prostate or cervix, [12]. Despite these inconsistencies, the clinical reality is that lung cancer occurring as a second primary malignancy currently accounts for between 8-14% of all lung cancer diagnoses [15], [16], [17], [18], [19]. As lung cancer screening becomes more widely used, the potential inclusion of certain cancer survivors in lung cancer screening programs needs to be more systematically addressed.…”
Section: Discussionmentioning
confidence: 99%
“…For example in the studies referenced above, 1 excluded patients with any history of cancer [10], 1 included patients with a history of smoking related cancers [8], 1 excluded patients with a history of cancer within 5 years, 1 excluded patients with a history of renal cancer, melanoma or breast cancer [14], while 2 excluded most cancer patients with exception of non-melanomatous skin cancer, and in-situ carcinoma of the bladder [2], prostate or cervix, [12]. Despite these inconsistencies, the clinical reality is that lung cancer occurring as a second primary malignancy currently accounts for between 8-14% of all lung cancer diagnoses [15], [16], [17], [18], [19]. As lung cancer screening becomes more widely used, the potential inclusion of certain cancer survivors in lung cancer screening programs needs to be more systematically addressed.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors had reported similar finding like ours, where lung cancer with a secondary malignancy had improved survival compared to those without secondary malignancy. [ 710 ] In our cohort, patients with secondary malignancy presents with earlier lung cancer stage and greater proportion of patient receiving surgical treatment. In the study by Hofmann et al, [7] the improved survival by patient with additional secondary malignancy is determined by a shift towards lower tumor stages and fewer SCLCs.…”
Section: Discussionmentioning
confidence: 99%
“…[ 710 ] In our cohort, patients with secondary malignancy presents with earlier lung cancer stage and greater proportion of patient receiving surgical treatment. In the study by Hofmann et al, [7] the improved survival by patient with additional secondary malignancy is determined by a shift towards lower tumor stages and fewer SCLCs. However, others had reported better survival for patients without a second malignancy or no difference.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most second primary lung cancers occur synchronously within 24 months to index head and neck cancer [7]. Oro-hypopharynx or larynx are the most common sites of index head and neck tumor and ‘squamous cell’ is the most common histological type of index head and neck tumor associated with second primary lung cancer development [8].…”
Section: Discussionmentioning
confidence: 99%